2020
DOI: 10.32615/ps.2019.179
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Environmental pollution is reflected in the activity of the photosynthetic apparatus

Abstract: The efficiency of chlorophyll (Chl) fluorescence for forecasting plant response to environmental pollution was examined in four wheat cultivars. The plants were irrigated with wastewater from Razi petrochemical complex. A forecasting model was designed based on the data of maximal quantum yield of photosystem II (Fv/Fm), efficiency of both photosystems (PIABS), and Chl contents of 60-d analysis. A comparison of the forecasting model results with the real data of Fv/Fm, PIABS, and Chl in response to wastewater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…It is known that the photosynthetic apparatus of plants in general and their chlorophyll level in particular are very sensitive to unfavorable factors. Despite the fact that, in some studies, it was shown that content of chlorophylls is not an accurate tool for forecasting plant response to environmental stress [ 40 ], the content of photosynthetic pigments in leaves turns out to be an indirect indicator reflecting the efficiency of photosynthesis. As shown in previous research [ 41 ], mechanisms of inhibitory effects of polycyclic aromatic hydrocarbons on photosynthetic processes includes damage to the lipid bilayer of the plasma membrane and then violation of lipid bilayer membranes of cell organelles and generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the photosynthetic apparatus of plants in general and their chlorophyll level in particular are very sensitive to unfavorable factors. Despite the fact that, in some studies, it was shown that content of chlorophylls is not an accurate tool for forecasting plant response to environmental stress [ 40 ], the content of photosynthetic pigments in leaves turns out to be an indirect indicator reflecting the efficiency of photosynthesis. As shown in previous research [ 41 ], mechanisms of inhibitory effects of polycyclic aromatic hydrocarbons on photosynthetic processes includes damage to the lipid bilayer of the plasma membrane and then violation of lipid bilayer membranes of cell organelles and generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…As the photosynthesis is one of the most important physiological processes for plants to obtain carbon [ 26 ]. When drought stress causes a decrease in photosynthesis, trees are vulnerable to carbon starvation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the competition between these three processes, ChlF can be used to obtain photosynthesis information (Maxwell & Johnson, 2000;Murchie & Lawson, 2013). In recent years, researchers have used the changes of ChlF to explore photosynthetic apparatus under different environmental situations (Badr & Brueggemann, 2020;Hajihashemi et al, 2020;Iqbal et al, 2019;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%